Challenges in Identifying and Determining the Impacts of Infection with Pestiviruses on the Herd Health of Free Ranging Cervid Populations - Ridpath, Julia F.; Neill, John D. (Frontiers in Microbiology, 2016)
Although most commonly associated with the infection of domestic livestock, the replication of pestiviruses, in particular the two species of bovine viral diarrhea virus (BVDV), occurs in a wide range of free ranging cervids including white-tailed deer, mule deer, fallow deer, elk, red deer, roe deer, eland and mousedeer. While virus isolation and serologic analyses indicate that pestiviruses are circulating in these populations, little is known regarding their impact. The lack of regular surveillance programs, challenges in sampling wild populations, and scarcity of tests and vaccines compound the difficulties in detecting and controlling pestivirus infections in wild cervids. Improved detection rests upon the development and validation of tests specific for use with cervid samples and development and validation of tests that reliably detect emerging pestiviruses. Estimation of impact of pestivirus infections on herd health will require the integration of several disciplines including epidemiology, cervid natural history, veterinary medicine, pathology and microbiology.